"Plata o Plomo?": Bribe and punishment in a theory of political influence - Ernesto Dal Bó; Pedro Dal Bó; Rafael di Tella (Brown University, Department of Economics, 2002)
We present a model where groups attempt to exert influence on policies using both bribes (plata, Spanish for silver) and the threat of punishment (plomo, Spanish for lead). We then use it to make predictions about the quality of a country's public officials and to understand the role of institutions granting politicians with immunity from legal prosecution. The use of punishment lowers the returns from public office and reduces the incentives of high ability citizens to enter public life. Cheaper plomo and more resources subject to official discretion are associated with more frequent corruption and less able politicians. Moreover, the possibility of punishment changes the nature of the influence game, so that even cheaper plata can lower the ability of public officials. Protecting officials from accusations of corruption (immunity) will decrease the frequency of corruption and may increase the quality of politicians if the judiciary is weak. These predictions are the opposite to those emerging from a model where only bribes are used. – lobbying ; threats ; quality of policymakers ; official immunity
Keywords: D72; D78; K4; 330; Interessenpolitik; Interessenvertretung; Korruption; Theorie